Can a surgery-first orthognathic approach reduce the total treatment time?. Issue 4 (April 2017) - Jeong, Woo Shik; Choi, Jong Woo; Kim, Do Yeon; Lee, Jang Yeol; Kwon, Soon Man
Abstract: Although pre-surgical orthodontic treatment has been accepted as a necessary process for stable orthognathic correction in the traditional orthognathic approach, recent advances in the application of miniscrews and in the pre-surgical simulation of orthodontic management using dental models have shown that it is possible to perform a surgery-first orthognathic approach without pre-surgical orthodontic treatment. This prospective study investigated the surgical outcomes of patients with diagnosed skeletal class III dentofacial deformities who underwent orthognathic surgery between December 2007 and December 2014. Cephalometric landmark data for patients undergoing the surgery-first approach were analyzed in terms of postoperative changes in vertical and horizontal skeletal pattern, dental pattern, and soft tissue profile. Forty-five consecutive Asian patients with skeletal class III dentofacial deformities who underwent surgery-first orthognathic surgery and 52 patients who underwent conventional two-jaw orthognathic surgery were included. The analysis revealed that the total treatment period for the surgery-first approach averaged 14.6 months, compared with 22.0 months for the orthodontics-first approach. Comparisons between the immediate postoperative and preoperative and between the postoperative and immediate postoperative cephalometric data revealed factors that correlated with the total treatment duration. The surgery-first orthognathic approach can dramatically reduce the total treatment time, with no major complications.